2010
DOI: 10.1002/jor.21078
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Wnt signaling influences fracture repair

Abstract: While the importance of Wnt signaling in skeletal development and homeostasis is well documented, little is known regarding its function in fracture repair. We hypothesized that activation and inactivation of Wnt signaling would enhance and impair fracture repair, respectively. Femoral fractures were generated in Lrp5 knockout mice (Lrp5−/−) and wild-type littermates (Lrp5+/+), as well as C57BL/6 mice. Lrp5−/− and Lrp5+/+mice were untreated, while C57BL/6 mice were treated 2×/week with vehicle or anti-Dkk1 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 23 publications
4
92
0
1
Order By: Relevance
“…Similar results as those reported for sclerostin antibodies have also been reported with blocking or down regulation of Dkk1 expression. Dkk1 antibodies enhance endochondral bone healing in LRP5 deficient mice [16]. Inhibition of Dkk1 can counter some of the effects of oestrogen deficiency in rats, restoring bone mineral content and density [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results as those reported for sclerostin antibodies have also been reported with blocking or down regulation of Dkk1 expression. Dkk1 antibodies enhance endochondral bone healing in LRP5 deficient mice [16]. Inhibition of Dkk1 can counter some of the effects of oestrogen deficiency in rats, restoring bone mineral content and density [35].…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal trauma causes a local increase in Wnt signaling [11] and it has been shown that the pathways involved in bone Wnt signaling are necessary for bone healing [11][12] and for bone formation in general [13][14][15]. Fracture repair can be influenced by blocking Dkk1 in mice [16] and a decrease in Dkk1 gene expression leads to an increase in bone mass and strength [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Wnt factors are suspected to relay the early indirect effects of TNF-a in AS [10] and during bone repair [11][12][13]. Wnt proteins are a family of 19 highly conserved secreted glycoproteins that play essential roles during development and tissue homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Next, the current study injects Scl-Ab a week after the fracture, which may have undercut the beneficial effectiveness of the treatment during the first week of healing. Delayed injection post fracture of a different monoclonal antibody of a negative regulator of the Wnt pathway, DKK1, impaired its benefit compared to injections immediately postfracture [3]. Therefore, what are the consequences of early as well as late Scl-Ab treatment?…”
Section: Corr Insightsmentioning
confidence: 99%